ROLE OF SYMPTOMATIC TREATMENT IN COMPARISON TO ANTIBIOTICS IN UNCOMPLICATED URINARY TRACT INFECTIONS - Jamil, Muhammad Nasir; Farooq, Umer; Sultan, Babar; Khan, Raza Muhammad (Journal of Ayub Medical College Abbottabad, 2016)
Background: Uncomplicated urinary tract infections (UTIs) are the most common bacterial infections among women presenting to primary care causing rapidly increasing strains of resistant bacteria to the growing antibiotic industry. Restricting antibiotics to necessary indications is the only solution. The objectives of the study were to compare the efficacy of symptomatic treatment vs antibiotic in patients with uncomplicated UTI, in terms of individual symptom score, i.e., frequency, urgency, dysuria, supra pubic pain scores and total symptoms scores. Methods: A randomized control trial (RCT) in 100 women (15-50 years) with symptoms of urinary frequency, urgency, dysuria and pain supra pubic region, associated with uncomplicated UTI, at Urology department, AMI, Abbottabad. Two treatment strategies were compared in uncomplicated UTI patient). Patients were randomized to antibiotic or symptomatic treatment groups on consecutive non-probability basis (50 in each group) given for 05 days. Efficacy of medications was assessed by comparing pre and post treatment symptom scores along with the post treatment scores of both groups compared to see statistical significance of difference by independent samples t-test. Results: There was a statistically significant difference in symptoms improvement in both treatment arms of all scores, i.e., p-value=0.000. Whereas only dysuria score was able to show a statistically significance of difference in post Rx scores comparison of both groups, p-value=0.004. Conclusions: Symptomatic treatment is not inferior to antibiotic treatment when proper patient selection is undertaken, resulting in decreased need for unnecessary antibiotics use. Keywords: Uncomplicated; Urinary tract infections; Symptom score; Antibiotics; Symptomatic treatment